2021
DOI: 10.21037/qims-20-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of dual-energy computed tomography for differentiating metastatic and non-metastatic lymph nodes of colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is the third most common malignancy worldwide, and lymph node metastasis is considered to be a risk factor for local recurrence and a poor prognosis in colorectal cancer.However, there remains a lack of reliable and non-invasive biomarkers to identify the lymph node status of CRC patients preoperatively. The purpose of this study was to explore the ability of dual-energy computed tomography (DECT) to differentiate metastatic from non-metastatic lymph nodes in colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…Thus, it may be that more contrast agents were retained in the tumor blood vessels in the low-risk group in the VP, resulting in the higher VP-NIC in the low-risk group than in the high-risk group. Nevertheless, there were no significant differences between the two groups in terms of electron density and effective atomic number, and the results support those of Qiu et al ( 32 ). However, Zhang et al ( 33 ) found that the normalized effective atomic number value of metastatic sentinel lymph nodes in breast cancer patients was significantly larger than that of non-metastatic lymph nodes.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it may be that more contrast agents were retained in the tumor blood vessels in the low-risk group in the VP, resulting in the higher VP-NIC in the low-risk group than in the high-risk group. Nevertheless, there were no significant differences between the two groups in terms of electron density and effective atomic number, and the results support those of Qiu et al ( 32 ). However, Zhang et al ( 33 ) found that the normalized effective atomic number value of metastatic sentinel lymph nodes in breast cancer patients was significantly larger than that of non-metastatic lymph nodes.…”
Section: Discussionsupporting
confidence: 89%
“…ROC analysis of the different parameters of DECT in thyroid carcinomas with and without lymph node metastasis (IC mg/mL, CT value HU) HU in metastatic lymph nodes compared to nonmetastatic lymph nodes in thyroid carcinoma(34)(35)(36), it was difficult to measure the parameters of all lymph nodes for all patients, and a portion of the lymph nodes were illegible. It was relatively easy and feasible to measure the lesion of thyroid carcinoma, which may indirectly reflect the status of the lymph nodes in thyroid carcinoma.…”
mentioning
confidence: 99%
“…The mean age of patients in the 16 included studies varied from 34.0±7.8 to 59.5±8.7 years, while the percentage of males ranged from around 0.0% to 70.9%. Moreover, 7 of the 16 studies included patients with thyroid cancer ( 16 , 23 , 24 , 29 , 30 , 33 , 36 ), 4 studies included patients with colorectal cancer ( 25 , 28 , 35 , 37 ), and the remaining 5 studies included patients with esophageal cancer, liver cancer, breast cancer, squamous cell carcinoma of the oropharynx, or lung cancer ( 26 , 27 , 31 , 32 , 34 ). Table 1 details the patient characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…After a reading of the titles and abstracts of these 257 original studies, 202 papers were excluded. Then, full texts were read in detail, and a rescreening was performed based on the inclusion and exclusion criteria, resulting in a final sample of 16 eligible studies for inclusion in this meta-analysis (16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The flowchart outlining the screening process is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation